Nostoc cyanobiont in the Cyanolichen, Sticta weigelii of Eastern Himalayan Region: Isolation, Physiological and Biochemical Characterization - Hynniewta, Athokpam Pinokiyo*, Mayashree B. Syiem*, Luxemburgh (Journal of Experimental Sciences, 2011)
A cyanobacterium identified as Nostoc sp. was isolated from the cyanolichen, Sticta weigelii (Ach.) Vainio collected from tree barks in the state of Meghalaya and its various physiological and biochemical characters were evaluated. When the lichen thalli were incubated in liquid medium, the Nostoc colonies from these thalli appeared initially in distinct sacs that released individual long heterocystous filaments into the liquid medium upon sub-culturing. The well spaced heterocystsin the filaments had a frequency of 7-8%. Chlorophyll a concentration of the cyanobacterium was higher in comparison to many other Nostoc species isolated from soil and water from the same region. Its photosynthetic activity was 519.24±0.7 nmol O2 evolved µg-1 chl a h-1 whereas respiration was 286.35±0.5 nmol O2 consumed µg-1 chl a h-1. Enzyme assays reflected nitrogenase activity of 6.98 nmol C2H4 produced µg-1 chl a h-1 and GS transferase activity of 712±3.0 nmol γ-glutamyl hydroxymate formed min-1 mg-1 protein. Nitrate reductase activity was substrate inducible. Ammonium uptake was biphasic in nature and glutamine uptake was energy dependent.